Pengembangan dan Evaluasi Printer 3D FDM Berbasis Linear Slider MGN12 untuk Meningkatkan Kepresisian pada Aplikasi Ergonomi dan Industri - Akbar, Ridho; Ardina Kusuma, Yessie; Poniman, Poniman; Hakim, M. Hanifuddin; Arifa P.A, Eldisyah; Afli A., Rendie (SURYA TEKNIKA, 2024)
Three-dimensional (3D) printing technology, particularly the Fused Deposition Modeling (FDM) method, plays a crucial role in modern industrial design and ergonomics research. One of the primary challenges in this application is ensuring high precision, operational stability, and reducing mechanical wear to support the sustainability and efficiency of the printing process. This study introduces the development of a 3D printer based on FDM, utilizing the MGN12 linear slider as a replacement for conventional roller bearings. This innovation is designed to improve printing accuracy, optimize component durability, and maintain long-term operational quality. Empirical testing was conducted to compare the performance of the linear slider system and roller bearings in terms of dimensional accuracy, surface finish, printing speed, and mechanical durability. The results show that the linear slider system achieves dimensional accuracy of up to ±0.02 mm, better than the ±0.12 mm of the roller bearing system. The average surface roughness also decreased to 3.2 µm, compared to 5.6 µm in the roller bearing system. At high printing speeds (150 mm/s) with a layer height of 0.01 mm, the roller bearing system exhibited greater inconsistency, producing an average layer height of 0.04 mm, while the linear slider maintained high layer consistency. Additionally, the linear slider system reduced noise levels to 45 dB and significantly minimized mechanical wear, thereby reducing the need for regular maintenance. The findings of this study indicate that although the initial investment in linear slider technology is higher, it provides a significant improvement in 3D printing performance. This technology is highly relevant for industrial applications requiring high precision, process efficiency, and system reliability.